N-nitrosation of secondary amines using p-TSA-NaNO2 as a novel nitrosating agent under mild conditions - Borikar, Sanjay P.; Paul, Vincent (Synthetic Communications, 2010)
A combination of p-toluenesulfonic acid (p-TSA) and sodium nitrite was used as a novel effective nitrosating agent for the N-nitrosation of secondary amines to their corresponding nitroso derivatives under mild and heterogeneous conditions in moderate to excellent yields.
Keywords: N-nitrosation; nitroso amines; p-toluenesulfonic acid; secondary amines